Al Insaf fi masail al khilaf bayna al nahwiyin, al basriyyin, wa alkufiyyin - Shaykh al Imam Kamaluddin Abi Barkat Abdurrahman ibn Muhammad ibn Abdullah ibn abi Sa'id al Anbari (Maktab wa matba'ah Muhammad Ali Sabih, 1953)
sn, jl.1,c.1-5; jl.2,c.1-2